1999
DOI: 10.2337/diabetes.48.4.927
|View full text |Cite
|
Sign up to set email alerts
|

Hyperglycemia causes oxidative stress in pancreatic beta-cells of GK rats, a model of type 2 diabetes.

Abstract: Reactive oxygen species are involved in a diversity of biological phenomena such as inflammation, carcinogenesis, aging, and atherosclerosis. We and other investigators have shown that the level of 8-hydroxy-2'-deoxyguanosine (8-OHdG), a marker for oxidative stress, is increased in either the urine or the mononuclear cells of the blood of type 2 diabetic patients. However, the association between type 2 diabetes and oxidative stress in the pancreatic beta-cells has not been previously described. We measured th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
311
2
5

Year Published

2000
2000
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 463 publications
(341 citation statements)
references
References 0 publications
21
311
2
5
Order By: Relevance
“…These results are consistent with previous results showing that c-myc expression is induced after partial pancreatectomy model of diabetes and in rats maintained with a hyperglycemic clamp (9,10). Since the diabetic state is associated with PKC activation (13)(14)(15)(16)(17)(18)(19)(20) and the production of reactive oxygen species in several cell types (27)(28)(29)(30)(31), the involvement of PKC and oxidative stress in c-myc induction was studied. As shown in Fig.…”
Section: Induction Of C-myc Gene Expression In Rat Pancreatic Islets supporting
confidence: 89%
“…These results are consistent with previous results showing that c-myc expression is induced after partial pancreatectomy model of diabetes and in rats maintained with a hyperglycemic clamp (9,10). Since the diabetic state is associated with PKC activation (13)(14)(15)(16)(17)(18)(19)(20) and the production of reactive oxygen species in several cell types (27)(28)(29)(30)(31), the involvement of PKC and oxidative stress in c-myc induction was studied. As shown in Fig.…”
Section: Induction Of C-myc Gene Expression In Rat Pancreatic Islets supporting
confidence: 89%
“…The high urinary 8-OHdG levels in the patients with high albuminuria investigated in this study suggested that the increased oxidative stress has a primary role in the pathogenesis of diabetic nephropathy. Recent reports found an increased systemic oxidative stress in diabetic patients and in diabetic animal models [13,[21][22][23]. Our study showed that the patients with normoalbuminuria had a lower urinary 8-OHdG level than the patients with high albuminuria.…”
Section: Resultssupporting
confidence: 60%
“…3a) when compared with untreated normal animals. It has been reported that impaired GSIS observed in GK rats is associated with alterations in β-cell glucose metabolism, protein kinase C pathway, modulation of UCP-2 expression, acetylcholine and oxidative stress [11,26,[47][48][49]. However, it can also be associated with fatty acid content alterations.…”
Section: Discussionmentioning
confidence: 99%